Mapping of the Madiun historical cites - Muhammad Hanif (UNIVERITAS PGRI MADIUN, 2023)
This research aims to map Madiun historical sites. Given that some historical relics around Madiun have developed to be used as recreational functions or tourist attractions, but the public is still a lot of little information. The research was conducted in Madiun Regency and City for one year using the historiography method. This method moves through heuristic techniques, source criticism, interpreting facts and writing narratives according to field findings. The historical stories of the site were successfully reconstructed, then made into thematic maps in the form of traditional and digital maps. The results of the research found 17 sites that have important value in the history of Madiun, which are located in the administrative areas of Madiun Regency and Madiun City. Even though it includes two government areas, the road to the location is in good condition. The map of Madiun historical sites in the convention described is well mapped on conventional and digital historical maps. The maps that were successfully made in both traditional and digital forms were classified as good because they met the criteria of equidistance, equivalence, suitability, complete information and easy to understand. The findings of this research are so important so that the heritage of the past is not eroded by the times and the community needs to be made aware of knowledge information on Madiun's local wisdom.